1979
DOI: 10.1084/jem.150.4.830
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphocyte response to cytochrome c. I. Demonstration of a T-cell heteroclitic proliferative response and identification of a topographic antigenic determinant on pigeon cytochrome c whose immune recognition requires two complementing major histocompatibility complex-linked immune response genes.

Abstract: The T-lymphocyte proliferative response to pigeon cytochrome c was studied in the mouse. H-2a and H-2k strains were responders to this antigen whereas H-2b, H-2d, H-2f, H-2ja, H-2p, H-2q, H-2r, H-2s, and H-2u strains were low or nonresponders. Genetic mapping demonstrated that two major histocompatibility complex (MHC)-linked Ir genes control the response, one in I-A, the other in I-E/I-C. The major antigenic determinant recognized in this response was localized by cross-stimulations with species variants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(60 citation statements)
references
References 30 publications
(46 reference statements)
3
57
0
Order By: Relevance
“…A heteroclitic epitope describes an altered peptide that is a better agonist for inducing T cell responses than the native, unaltered peptide (13). This terminology has been applied to other altered peptides with a higher immunological potency than their unaltered counterparts (14 -16).…”
mentioning
confidence: 99%
“…A heteroclitic epitope describes an altered peptide that is a better agonist for inducing T cell responses than the native, unaltered peptide (13). This terminology has been applied to other altered peptides with a higher immunological potency than their unaltered counterparts (14 -16).…”
mentioning
confidence: 99%
“…ϩ T cells used model Ags, such as pigeon cytochrome c or hen egg-white lysozyme (5,6). Purified proteins from different animal species of cytochrome or lysozyme with known sequences were then tested for their ability to crossstimulate T cells.…”
mentioning
confidence: 99%
“…In rodents, short peptide sequences derived from the α 1 domain polymorphic region of rat class I RT1.A a induced sensitization against RT1 a allografts [12], provoked alloantibody production and T cell proliferative responses [13][14][15]. MHC alloantigens are therefore similar to multideterminant protein antigens that bear localized immunodominant a.a. sequences that trigger immune responses toward the whole protein molecule [2,[20][21][22]. This suggests that indirect allorecognition is amenable to specific immunointervention possibly through manipulation of such dominant immunogenic epitopes, similar to previous experiments that modified immunodominant determinants of multideterminant protein antigens.…”
Section: Introductionmentioning
confidence: 58%
“…Additionally, immediate epitope flanking residues, as well as, downstream sequences have been shown to play a crucial role in epitope recognition by responding T cells [42]. Although analysis of T cell responses to nominal protein or transplantation antigens has shown that constraints in antigen processing and presentation usually limit the T cell responses to one or two dominant determinants [1,8], there is also evidence highlighting the hierarchy of the polyclonal nature of the indirect T cell responses, suggesting the participation of multiple T cell determinants [12,13,[20][21][22]36]. We therefore hypothesize that [α 1h l/u ]-RT1.A a allochimeric molecules containing both dominant donor-type immunogenic epitopes and cryptic subdominant self-epitopes together orchestrate peri-operative transplantation tolerance through manipulation of the indirect pathway.…”
Section: Discussionmentioning
confidence: 99%